PENYULUHAN KESEHATAN: GANGGUAN MENSTRUASI PADA REMAJA - Perwiraningtyas, Pertiwi; Juwita, Linda (Stikes Yarsi Mataram, 2025)
Physiologically, adolescent girls experience menstruation every month, but sometimes menstruation is accompanied by disorders. Menstrual disorders can occur in three forms, namely pain (dysmenorrhea) before and during menstruation, menstrual cycles that are too long (oligomenorrhea) or too short (polymenorrhea), and/or excessive bleeding (hypermenorrhea) or too little bleeding (hypomenorrhea). These menstrual disorders can interfere with the quality of life and health of adolescent girls. The purpose of this community service activity is as an effort to reduce morbidity due to menstrual disorders and improve the health and quality of life of adolescent girls. The method used is health education and the provision of leaflets on menstrual disorders which are delivered in one meeting and continued with a discussion. This activity went well and was attended by approximately 40 nursing students. During the discussion process, the participants of the education seemed very enthusiastic, as shown by several questions submitted to the education worker both during the first and last discussion sessions. Educational institutions are expected to be able to organize routine health education activities for adolescent girls from an early age regarding menstrual disorders, as an effort to improve their health and quality of life